The structure of subclades of the Y-chromosome C haplogroup as evidence of Mongol migrations in the XIII, XVII and XVIII centuries - A. M. Tyurin (Nomadic Civilization: Historical Research)
Two major migrations of Mongols outside the territory of Mongolia are known. The first was in the process of the Mongol conquests of the XIII century. The second is the transition of the Oirat Mongols from Western Mongolia to Xinjiang, Semirechye and the Northern Caspian region in the first half of the XVII century, with the formation of the Dzungarian and Kalmyk khanates. There was also migration of Kalmaks (Dzungars) from the territory of the Dzungarian Khanate to other regions after its defeat by China in 1755-59. Within the framework of population genetics, two subpopulations are distinguished among the Mongols: the Oirat Mongols and the Khalkha Mongols (western and eastern Mongols). Both subpopulations participated in the first migration, and only the OiratMongols participated in the second and third. In terms of frequencies, different subclades of the Y-chromosome C haplogroup dominate in subpopulations. Based on this, it is possible to set the task of separately searching for genetic traces of Mughal migration in the XIII century, as well as Oirat migrations in the XVII and XVIII centuries in the gene pool of populations of Eastern Europe and Asian regions. The subclades of haplogroup C are allocated in the YTree Tree: C-Y11591 «Sungir», C-K281 «Kostenki», C-M8574 «Unidentified», C-Y10418 «Avars», C-M48 «Kalmyks», C-M504 «Khazarians» and C-F1067 «Mongols-Khalkha (?)». Their ethnogeography is considered. The subclades «Kalmyks» and «Khazarians» are Oirat. The subclade «Mongols-Khalkha (?)» presumably refers to the Khalkha Mongols. Genetic traces of the migration of the Oirat Mongols in the XVII and XVIII centuries have been revealed the Tatars of Tatarstan, Tomsk, Nizhny Novgorod and Ryazan regions. Tatars, carriers of haplogroup C, are their descendants.